Ready, Steady, Study: Implications of Online Learning for Early Childhood Teacher Education - Karen du Plessis; Lisa Walker; Christopher Naughton (Flexible Learning Association of New Zealand, 2012)
Online learning is a relatively new mode of study for educating early childhood teachers in New Zealand. This review discusses online learning and the need for preparation to learn in an online environment. Following a comparison of traditional and online modes of study, the paper reviews online learning in general and relates it to the early childhood context. The importance of a dedicated orientation for early childhood student teachers in an online learning environment is fully justified.